USIA IBU, ANEMIA, DAN KEJADIAN PARTUS PREMATUR DI RUANG MAWAR RSUD dr. M.YUNUS BENGKULU - Metha Fahriani; Reli Aprilawanti (Jurnal Sains Kesehatan, 2017)
Preterm labor is dangerous because of the potential increase of about 65-67% of perinatal mortality. The purpose of this study was to determine the relationship between  maternal age and incidence of anemia in preterm parturition in                       dr. M. Yunus Hospital Bengkulu. This type of research was Analytic Survey with study design Case Control with a ratio of 1: 1. The population in this study was mothers who numbered 1,434 people delivering mothers were taken by Total Sampling as many as 53 people (50%) mothers who have parturition premature for cases and  Systematic Random Sampling as many as 53 people (50%) mothers who did not experience parturition premature to control which totaled 106. The computerized data analysis using chi-square test. The results showed that of the 53 mothers who are 36 premature parturition with age 20 or 35 years and 30 people suffering from anemia. Of the 53 mothers who no premature parturition are 16 age 20 or 35 years and 15 suffer from anemia. There is a relationship between age and preterm parturition in the CI Midwifery dr. M. Yunus Hospital Bengkulu with the medium category. There is a relationship between anemia and preterm parturition in the CI Midwifery dr. M. Yunus Hospital Bengkulu with the closeness of the relationship that are in the weak category. It was expected to health worker, especially mid wifery in midwifery room to perform counseling about anemia and the importance  of  control  when  pregnant.Keywords :  age, anemia, premature partus